ANTIOXIDANT ACTIVITIY OF ADLAY EXTRACT (Coix lachryma-jobi L.) WITH DIFFERENT SOLVENT - Tensiska Tensiska; Bambang Nurhadi; Endah Wulandari; Yushini Ayu Laras Ratri (BPFP Faperta UNIB, 2020)
Adlay is a minor cereal which utilization is not optimal in Indonesia. Adlay grains have natural antioxidants in the form of phenolic compounds and flavonoids found in bran, husk, and testa. Purpose of this study was to determine the type of adlay bran extraction solvent that produced the highest antioxidant activity. The study used an experimental method with a randomized block design (RBD) consisting of 3 treatments that were repeated 4 times, namely extraction with (1) ethanol solvent; (2) n-hexane solvent; and (3) ethanol solvent then the waste is extracted again with hexane solvent. The extract obtained was analyzed for its antioxidant activity by DPPH method, total phenol, total tocopherol and yield. The results showed extracts from ethanol solvents produced the highest antioxidant activity where IC50 values were 771.73 ppm, but categorized as antioxidants with very weak activity. The extraction of adlay bran with ethanol solvent resulted in a yield of 1.91%, total phenol of 0.92%, and total tocopherol 0.09 mg / mL